Screening for distress in pediatric cancer survivors: A systematic comparison of one-step and two-step strategies to minimize detection errors. Issue 4 (4th July 2022) - Pépin, Annie-Jade; Lippé, Sarah; Drouin, Simon; Krajinovic, Maja; Laverdière, Caroline; Michon, Bruno; Robaey, Philippe; Rondeau, Émélie; Sinnett, Daniel; Sultan, Serge
Abstract: Background: Childhood cancer survivors should be routinely screened for psychological distress. However, existing screening tools promoted by cancer care institutions, such as the Distress Thermometer (DT) generate high rates of errors. The aim of this study is to help refining strategies of screening psychological distress in this population by exploring two-step methods combining the DT on step #1 with one question on step #2. Procedure: Data from 255 survivors of childhood acute lymphoblastic leukemia aged 13–40 years were analyzed (38% 13–18 years, 62% 19+ years, 53% females). We used the DT on step #1 and the individual emotion items from the Pediatric Quality of Life Questionnaire (PedsQL) on step #2, to detect distress, depression and anxiety as measured by standard instruments. We compared sensitivity, specificity, negative and positive predictive values, Youden index, and clinical utility indices, in newly developed two-step strategies. Results: The best two-step strategies to screen anxious-depressive distress were DT ≥ 2 on step #1, with the item of Sadness on step #2, and DT ≥ 2 combined with the item of Concerns. Two-step strategies outperformed the DT alone on the correct identification of distressed survivors. However, two-step strategies did not outperform the DT used alone on the correct detection of no distressed survivors. Results were similar when predicting depression or anxiety alone. Conclusion: Completing the DT with one single question on emotions from the PedsQL may minimize the number of participants falsely identified as distressed, which could be particularly pertinent in resource-limited clinics.